Designing minimal microbial strains of desired functionality using a genetic algorithm. Issue 1 (December 2015) - Nair, Govind; Jungreuthmayer, Christian; Hanscho, Michael; Zanghellini, Jürgen
Abstract Background The rational, in silico prediction of gene-knockouts to turn organisms into efficient cell factories is an essential and computationally challenging task in metabolic engineering. Elementary flux mode analysis in combination with constraint minimal cut sets is a particularly powerful method to identify optimal engineering targets, which will force an organism into the desired metabolic state. Given an engineering objective, it is theoretically possible, although computationally impractical, to find the best minimal intervention strategies. Results We developed a genetic algorithm (GA-MCS) to quickly find many (near) optimal intervention strategies while overcoming the above mentioned computational burden. We tested our algorithm onEscherichia coli metabolic networks of three different sizes to find intervention strategies satisfying three different engineering objectives. Conclusions We show that GA-MCS finds all practically relevant targets for any (non)-linear engineering objective. Our algorithm also found solutions comparable to previously published results. We show that for large networks optimal solutions are found within a fraction of the time used for a complete enumeration.